Identifying 'public values' for marine and coastal planning: Are residents and non-residents really so different?. (1st November 2017) - Munro, Jennifer; Pearce, Joanna; Brown, Greg; Kobryn, Halina; Moore, Susan A.
Abstract: Planning and management for marine and coastal areas is often contentious, with competing interests claiming their preferences are in the 'public interest'. Defining the public interest for marine and coastal areas remains a wicked problem, however, resistant to resolution. A focus on more tangible 'public values' offers an alternative for policy and planning in specific contexts. However, ambiguity surrounds who or what constitutes the 'public', with stakeholder engagement often used as a proxy in marine and coastal research. In this study, the outcomes of participatory processes involving the public from diverse backgrounds and geographical locales were explored. A public participation GIS (PPGIS) survey was undertaken in the remote Kimberley region of Australia to identify the spatial values and management preferences for marine and coastal areas. Similarities and differences between the volunteer public (n = 372) and online panel respondents (n = 206); and for the volunteer public only, differences between residents (n = 118) and non-residents (n = 254) were assessed. Online panelists evidenced lesser quality mapping data and did not provide a reliable means of accessing 'public' values. Residents were more likely to map general recreational and recreational fishing values while non-locals were more likely to map biological/conservation and wilderness values. Overall, residents and non-residents were more alike than dissimilar in their mapping of values and management preferences, suggesting that the need to preference local views may be overstated, although there may be differences in policy priorities. Future research should focus on the breadth and representativeness of stakeholder interests to access the views of wider society and hence public values, rather than current approaches where local interests are often the primary focus of participatory stakeholder engagement. Highlights: Ambiguity surrounds who or what the 'public' is in marine and coastal research. Local interests are often a primary focus of participatory stakeholder engagement. Participatory processes involving diverse 'publics' were explored. Residents and non-residents are similar in their mapping of values and preferences. The need to preference local views may be overstated.